2017
DOI: 10.1136/bmjsem-2017-000279
|View full text |Cite
|
Sign up to set email alerts
|

Increased supraspinatus tendon thickness following fatigue loading in rotator cuff tendinopathy: potential implications for exercise therapy

Abstract: Background/aimExercise imparts a load on tendon tissue that leads to changes in tendon properties. Studies suggest that loading immediately reduces tendon thickness, with a loss of this response in symptomatic tendinopathy. No studies investigating the response of tendon dimensions to load for the rotator cuff tendons exist. This study aimed to examine the short-term effect of loading on the thickness of the supraspinatus tendon and acromiohumeral distance those with and without rotator cuff tendinopathy.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 29 publications
5
38
0
1
Order By: Relevance
“…Tendon thickness in degenerative tendinopathy was seen to be increased on ultrasound examination [39] and decreased after adequate treatment [40], which can explain our results. Tendon thickness is known to be increased after exercise [41], which also explains our results.…”
Section: Discussionsupporting
confidence: 84%
“…Tendon thickness in degenerative tendinopathy was seen to be increased on ultrasound examination [39] and decreased after adequate treatment [40], which can explain our results. Tendon thickness is known to be increased after exercise [41], which also explains our results.…”
Section: Discussionsupporting
confidence: 84%
“…Another common reason for exclusion was that the participants were not diagnosed with SAPS. Fifteen studies met the inclusion criteria; nine of the 15 addressed the first aim 21,29,31,32,[52][53][54][55][56] , three addressed the second aim 54,57,58 and six addressed the final aim 29,32,[59][60][61][62] . Of the nine studies that addressed the first aim, one also addressed the second aim 54 and two addressed the third aim 29,32 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 775 participants were included across the 15 studies (Tables 1, 2, and 3). In the nine studies that addressed the first aim 21,29,31,32,[52][53][54][55][56] , 472 participants were included (mean age (SD) ranging between 23 (4) and 65 (10) years). Three of nine studies (170 participants) only included athletes, drawn from a variety of sports [54][55][56] , and the remaining studies included the general population.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The differential effect of loading on normal and symptomatic RC tendons has also been investigated 19 . McCreesh et al, demonstrated that a RC muscle fatigue protocol leads to a short‐term decrease in acromiohumeral distance and swelling of the supraspinatus tendon in people with RC tendinopathy.…”
Section: Introductionmentioning
confidence: 99%